Unfair competition general clause in Peru: The good, the bad and the ugly - Rodríguez García, Gustavo M. (2017)
In this article, the author analyzes the prohibitive general clause and its role in the repression of unfair competition, serving as a stabilizer of the norm. On the other hand, it criticizes the approval of the precedent Caballero Bustamante because it opened the way to discretion with respect to the norm.